2021
DOI: 10.3390/ijms22168977
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Scrape Loading-Dye Transfer Assay for Non-Genotoxic Carcinogen Testing

Abstract: Dysregulation of gap junction intercellular communication (GJIC) is recognized as one of the key hallmarks for identifying non-genotoxic carcinogens (NGTxC). Currently, there is a demand for in vitro assays addressing the gap junction hallmark, which would have the potential to eventually become an integral part of an integrated approach to the testing and assessment (IATA) of NGTxC. The scrape loading-dye transfer (SL-DT) technique is a simple assay for the functional evaluation of GJIC in various in vitro cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 328 publications
0
9
0
Order By: Relevance
“…On the basis of the synthesis and critical review of the primary biomarkers identified and from relevant project work [ 67 , 68 , 69 , 74 , 214 , 215 ], the three CTA models are exemplified in the manner in which they can individually address the mechanisms and hallmarks of NGTxC as specified in the OECD IATA for NGTxC [ 3 ]. For the MIEs, the SHE CTA is able to address the cellular metabolism and receptor mechanisms of AhR signaling via CYP1B1, CYP2E1, epoxide hydrolase 1, GSH transferase and thioredoxin reductase.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…On the basis of the synthesis and critical review of the primary biomarkers identified and from relevant project work [ 67 , 68 , 69 , 74 , 214 , 215 ], the three CTA models are exemplified in the manner in which they can individually address the mechanisms and hallmarks of NGTxC as specified in the OECD IATA for NGTxC [ 3 ]. For the MIEs, the SHE CTA is able to address the cellular metabolism and receptor mechanisms of AhR signaling via CYP1B1, CYP2E1, epoxide hydrolase 1, GSH transferase and thioredoxin reductase.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…Figure 3 includes the most promising of the gene signalling markers that we identified. These can then be utilised for the assays or test methods being evaluated for the key events of the IATA in parallel work, as recently reported for epigenetic DNA methylation [ 30 ], gap junction [ 32 ], cell transformation [ 30 , 32 , 99 , 136 ], and similar work currently underway such as that for immune dysfunction (Corsini et al, paper in preparation), etc.…”
Section: Critical Elements To Include When Designing Transcriptomic T...mentioning
confidence: 99%
“…In 2020, an OECD expert group developed an IATA for NGTxCs and published a consensus paper describing the overarching IATA, with the molecular initiating events (MIE) of cellular metabolism and receptor interactions, followed by the early key events (KEs) of inflammation and immune dysfunction, mitotic signaling, and cell injury, leading to (sustained) proliferation, morphological transformation and tumor formation ( Jacobs et al, 2020 ). Several assay evaluations and reviews have been conducted and published in relation to epigenetics ( Desaulniers et al, 2021 ), cell transformation ( Colacci et al, 2023 ), gap junction ( Sovadinova et al, 2021 ), gene signaling ( Oku et al, 2022 ), cell proliferation and oxidative stress ( Veltman et al, 2023 ). These publications provide details on the next steps needed to facilitate developments that will have regulatory relevance for the safety assessment of NGTxCs.…”
Section: Introductionmentioning
confidence: 99%
“…While several methods can be used to evaluate the dysregulation of GJIC, many have limited throughput and require specialized equipment ( Sovadinova et al, 2021 ). The SL-DT assay is the most commonly used in vitro method for evaluating the impact of toxicants or carcinogens on GJIC with a proven potential for high-content analysis and screening (HCA/HCS) ( Dydowiczova et al, 2020 ; Sovadinova et al, 2021 ). The SL-DT assay has been widely employed to study alterations in GJIC caused by hundreds of chemicals, including NGTxC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation